THE PROBLEM CONNECTION RELIGION AND PERSON’S PSYCHOLOGICAL WELL-BEING - Stepura, Eugene (PSYCHOLOGICAL JOURNAL, 2019)
Religion is excellent means of psychological health maintaining and psychological well-being of a person. This may be religion’s main function at the modern stage of our civilization development. But at the same time religion may include elements, which do not contribute to psychological health and psychological well-being of believers and can lead to the manifestation of different kinds of pathological psychic states and deviant behaviour. There are psychological preconditions for the involvement of a person’s in a religion. But if an individual is religiously converted, it can lead to the adaptation of not only positive, but also negative aspects of religion. Religious conversion may happen in two ways: via personal mystical experience and via involvement in the religious tradition by studying, parenting, etc. We may admit that these ways often complement each other, and involvement in the religious tradition serve as the basis of personal spiritual experience interpretation. This leads us to the problem of spiritual experience maintenance (which can have psychopathological nature) by certain cultural traditions of different religious groups. And vice versa, there are some religious groups which sometimes try to impose their inhuman ideology on the society, using psychopathological manifestations of some individuals. It is especially dangerous for the society when religious ideas of pathological nature combine/mix with a political ideology. Nowadays religiously-oriented subjects are often introduced into the school and university programmes, so we deal with the problem of control over the contents of these subjects in order to check if there are any anti-humanistic and anti-democratic ideas or any ideas, which can harm psychological well-being of students. And, on the contrary, it is important to introduce into the programmes of religiously-oriented subjects such ideas, which can contribute to the psychological health and well-being of the students. Besides, the contents of religious subjects will not be always adequately perceived by a certain percent of pupils and students because of their cognitive sphere peculiarities. Therefore the requirement that these subjects should be exclusively optional is grounded not only on the legal and culturological, but also on the psychological basis.